Compositional variation in eye-infiltrating immune cells distinguishes human uveitis subtypes - Christian Concepcion; Yu Xia; Yulia Korshunova; Gregory W. Bligard; Amal Taylor; Michael A. Paley; Philip A. Ruzycki; Lynn M. Hassman (iScience)
Summary: Uveitis is a heterogeneous group of ocular inflammatory diseases that respond inadequately to empiric therapy, underscoring the need to define pathophysiologic subtypes. Toward this goal, we applied single-cell transcriptional and immune receptor profiling to ocular fluid biopsies from 23 patients with diverse clinical features. We found that a subset of ocular T cells undergoes local clonal expansion, indicating that antigens trigger uveitis in some patients. Infiltrates from HLA-B27 associated acute anterior uveitis (HLA-B27 AAU) were enriched in myeloid cells and innate immune signaling pathways, while chronic uveitis featured prominent adaptive immune cells and transcriptional programs, indicating that immunologic features distinguish uveitis subtypes. Clinical features including anatomic involvement were associated with additional variability in the immune cell profile. These insights highlight the potential for deep transcriptional profiling of ocular immune cells to reveal endotypes within uveitis.